Pengembangan Aplikasi Pengorganisasian Tim Pengembang Perangkat Lunak dengan Mempertimbangkan Kepribadian - Rony Hendiarto; Bayu Priyambadha; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In the past ten years, the process of software engineering is growing faster and also the development of software engineers should be able to follow the development of software engineering. Because of that, the project amount of software engineering is getting larger and variant. However, there are several obstacles in practices of software engineering. One of the most common obstacle is the inaccuracy of the composition of the software development team because of social problems and conflicts experienced by the team.The researcher found a direct correlation between the success achieved in particular job role and someone's personality. The composition of the team in software development project is a crucial factor that is able to failure of a software development project. Identifying that personality can be used to measure the compatibility of a software development team, so it is necessary to have a system that is able to accurately identify personality of a person as well as the suitability of work positions especially in software engineering. The system must be able to identify a person's personality. From the results of these personalities, the system is also able to determine recommendations software development positions based on their personality dimensions of Bigfive Personality Traits, including: Openness to Experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism. From the results of Bigfive Personality Dimension, the system is also able to compile a software development team in working on a software project. The result of this research is had a three actor, eighteen functional requirements and also system are tested with a hundred percent valid.